The degree to which middle school teachers in Jerash Governorate schools in Jordan possess technological competencies in light of the standards of total quality management - Odibat, Anas Adnan; AL_spoa, Majda Kalf (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the degree of middle-school teachers in Jordan possessing technological competencies in light of the standards of total quality management, and to know whether there are statistically significant differences attributable to gender, educational qualification and experience variables. The study used the descriptive method, and the tool was a questionnaire. It was distributed to a random sample of (202) male and female teachers in the intermediate stage in Jerash Governorate schools, and the results showed that The degree of middle school teachers’ ownership in Jordan of technological competencies obtained a total average (3.89 out of 5) with a (high) grade, and at the level of fields, the field of formulating the vision and plan got the highest average (4.11), followed by the field of information technology with an average of (4.08), then the field of transfer and dissemination of knowledge With an average of (4.01) and a fourth solution, the field of investment and employment of knowledge with an average of (3.78) and a fifth in the environment needed for the prosperity of knowledge with an average of (3.73) and all of them with a high estimate (and finally) and finally the field of educational administration with an average of (3.65) and an average estimate, and the results also revealed the presence of statistically significant differences at the level of (α) ≤0.05) In the degree to which middle school teachers in Jordan possess technological competencies in light of the standards of total quality management attributed to the variables of study in all fields and the tool as a whole; According to the gender, it was in the interest of females, and according to the educational qualification in favor of the undergraduate category and based on the results, the researcher presented a set of recommendations and proposals to upgrade technological competencies among middle school teachers in Jerash Governorate and all of Jordan.